The mediating role of cognitive flexibility in home–school co-education and psychological well-being among Chinese vocational college students - Chao Liu; Hanjuan Chen; Wenping Xu; Shuling Dai; Shan Lin; Shan Lin (Frontiers in Psychology)
ObjectiveThis study examines the mediating role of cognitive flexibility in the relationship between home-school co-education (H-SCE) and depressive symptom among vocational college students in urban and rural areas of China.MethodsUtilizing the Theory of Overlapping Spheres of Influence, this research explores how H-SCE influences depressive symptom, considering cognitive flexibility as a key mediating factor. The study utilized established scales, including the Inventory of Parent and Peer Attachment (IPPA) for parent-child relationships, the Student-Teacher Relationship Scale (STRS), the Cognitive Flexibility Inventory (CFI), and the Center for Epidemiologic Studies Depression Scale (CES-D10).ResultsA total of 1090 valid questionnaires were analyzed, revealing a significant negative correlation between H-SCE and depressive symptom. Cognitive flexibility was found to partially mediate this relationship, suggesting that enhanced cognitive adaptability, fostered through effective H-SCE, can reduce depressive symptom by helping students better cope with stressors.ConclusionThese findings underscore the importance of fostering strong collaboration between families and schools to enhance cognitive resilience and mitigate psychological challenges faced by vocational students, providing a foundation for targeted interventions to promote mental well-being.